2016
DOI: 10.1182/blood-2016-01-691618
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair of myeloma plasma cells correlates with clinical outcome: the effect of the nonhomologous end-joining inhibitor SCR7

Abstract: Key Points• Responders to melphalan therapy are characterized by slower rates of NER and DSB/R mechanisms and higher apoptotic rates.• The DSB/R inhibitor SCR7 enhances cytotoxicity of melphalan against myeloma plasma cells.DNA repair activity of malignant cells seems to influence therapeutic outcome and patients' survival. Herein, we investigated the mechanistic basis for the link between DNA repair efficiency and response to antimyeloma therapy. Nucleotide excision repair (NER), interstrand cross-links repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…Importantly, SCR7-pyrazine also inhibited the joining of different 5 0 -5 0 noncompatible ends, which requires processing of DNA breaks prior to ligation, and is dependent on classical NHEJ proteins [29,31]. This was also consistent with the observed inhibition of NHEJ by SCR7 [17][18][19][46][47][48]. Besides, similar to SCR7-cyclized, SCR7-pyrazine also showed specific inhibition of joining catalyzed by Ligase IV and their effect on Ligase III, Ligase I, and T4 DNA ligase-mediated joining was minimal in vitro.…”
Section: Scr7-cyclized and Scr7-pyrazine Inhibit Nhej In A Ligase Iv-supporting
confidence: 77%
“…Importantly, SCR7-pyrazine also inhibited the joining of different 5 0 -5 0 noncompatible ends, which requires processing of DNA breaks prior to ligation, and is dependent on classical NHEJ proteins [29,31]. This was also consistent with the observed inhibition of NHEJ by SCR7 [17][18][19][46][47][48]. Besides, similar to SCR7-cyclized, SCR7-pyrazine also showed specific inhibition of joining catalyzed by Ligase IV and their effect on Ligase III, Ligase I, and T4 DNA ligase-mediated joining was minimal in vitro.…”
Section: Scr7-cyclized and Scr7-pyrazine Inhibit Nhej In A Ligase Iv-supporting
confidence: 77%
“…This is consistent with previous findings that rs25487 primarily impacts the DNA repair function of XRCC1 protein, not the mRNA and protein expression of XRCC1 . One laboratory has published PBMCs in MM patients metabolize melphalan similarly to BMPCs . Hence, it is likely that myeloma cells from patients carrying rs25487 AA/AG have impaired XRCC1‐mediated DNA repair activity and are more susceptible to melphalan‐induced DNA damage.…”
Section: Resultssupporting
confidence: 90%
“…Like other DNA‐alkylating agents, melphalan induces DNA damage through DNA alkylation and DNA interstrand crosslinks (ICLs) in cells (Figure ). It is assumed that the ability of myeloma cells to excise melphalan monoadducts and ICLs is central to the sensitivity to melphalan therapy as myeloma cells with effective DNA repair capacity are more likely to survive after HDM treatment . It is known that the nucleotide excision repair pathway (NER) and the base excision repair pathway (BER) play pivotal roles in the repair of melphalan‐induced monoadducts, whereas the single‐ and double‐strand break repair pathways (SSBR and DSBR) are involved in the repair of melphalan‐induced interstrand crosslinks (ICLs) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with regard to melphalan sensitivity, PBMC response to melphalan strongly correlates with bone marrow plasma cells (BMPCs) . Recently, it has been shown that responders to high dose melphalan‐based autologous stem cell transplantation have slower rates of excision repair and double‐strand breaks repair rates compared to non‐responders . Taken together, these findings suggest that transcriptional and post‐transcriptional regulation of p53 contributes to a patient's overall response to melphalan.…”
Section: Introductionmentioning
confidence: 99%
“…The p14ARF‐MDM2‐p53 axis is one of the primary pathways regulating p53 (Figure ) . The MDM2 oncoprotein specifically binds to the N‐terminal transactivation domain of p53 and represses its ability to activate transcription, thus down‐regulating p53‐mediated apoptosis .…”
Section: Introductionmentioning
confidence: 99%